EZH2 inhibition and 5-azacytidine enhance antitumor immunity in PTEN-deficient glioblastoma by activation viral mimicry response - Xiao Xiao; Yong Li; Dandan Zhu; Huolun Feng; Zuda Huang; Jieqing Guo; Jiabin Zheng; Fan Xing; Zeying Li; Liangying Zheng; Fa Ling (Journal for ImmunoTherapy of Cancer)
Background PTEN-deficient glioblastoma (GBM) is characterized by an immunosuppressive tumor microenvironment (TME), therapeutic resistance, and poor prognosis. Emerging evidence suggests that dysregulation of the endogenous retrovirus (ERV)-MAVS-IFN pathway may contribute to immune evasion in cancer, but its role in PTEN-deficient GBM remains unclear.Methods Using flow cytometry and single-cell RNA sequencing, we analyzed the immune landscape of PTEN-deficient GBM. We evaluated the effects of 5-azacytidine (5-AZA) monotherapy and its combination with EZH2 inhibition (EZH2i) on ERV reactivation, type I interferon (IFN) responses, and TME remodeling. Mechanistic studies focused on H3K27me3-mediated epigenetic regulation of ERV expression.Results We found that PTEN deficiency suppresses type I IFN responses by impairing viral mimicry through dysregulation of the ERV-MAVS-IFN pathway, thereby sustaining an immunosuppressive TME. While 5-AZA alone failed to reactivate ERVs or overcome therapeutic resistance, combining it with EZH2i synergistically restored robust type I IFN signaling. This combination therapy reduced H3K27me3 levels, promoting ERV transcriptional activation and enhancing 5-AZA-induced viral mimicry. Consequently, the dual treatment reprogrammed the TME to boost antitumor immunity and suppress tumor progression.Conclusions Our study demonstrates that PTEN-deficient GBM evades immune surveillance by suppressing the ERV-MAVS-IFN axis. The combination of EZH2i and 5-AZA overcomes this resistance by epigenetically reactivating viral mimicry, offering a promising therapeutic strategy to enhance antitumor immunity and improve outcomes in patients with PTEN-deficient GBM.